Assessment of florsstic composition of forest undergrowth of international institute of iropscal agriculture (iita) forest reserve Ibadan, -Nigeria. (2014)
Assessment of understorey species of a tropical rainforest ecosystem in South-western Nigeria, exemplified by International Institute of Tropical Agriculture (IITA) forest reserve, Ibadan. A total of twenty-four permanent sample plots of 0.0625 ha were used for the assessment of understorey composition, density and frequency. Relative frequency, Relative Density and Importance Value Index (TVT), similarity, diversity and Detrended Correspondence Analaysis (DCA) statistics were used to analyse the data. The result showed a total of 3,833 individual from 128 species and 44 families (28 shrub, 57 trees, 33herbs, 2 grasses and 8 climbers ) were identified. Papilonaceae had the height number of species (11) followed by Moraceae (10), Albizia zygia had the height frequency of occurency (24), density of 169.33/ha. However Culcasia scandens had the height density of 299.33/ha. Highest Importance value index of 13.82 was recorded for Culcasia scandens, followed by Chromolaena odorata (11.80). The.least (IVI) 0.18 was recorded for Blepharis maderaspatensis, Carica papaya, Cissus pinata. Similarity between paired plots varied from 0.16 to 0.75, Simpson diversity (0.9529) and dominance of 0.0471, number of species present in each of the plotranged from 0-39. Plot 84 had the heighest species (39), high Eigen value (73.7%), length of. ordination space (-2 to 6) and the location of all the plots in the first quadrant indicated that the environment was stable indicative of minimal variation in floristic composition between plots and high heterogeneity of the site and species respectively. These findings showed that the IITA forest is diverse in species composition and the diversity of the understory may act as a catalyst for successful natural forest succession. Hence may be creating a more favourable environment for the establishment of native forest flora and habitat for fauna. Ultimately may be leading to conserving biological diversity. The study eventually concluded that a proper protection from human interferences and scientific management of undergrowth of the study area may lead to biodiversity rich site in the country.